Factors of Financial Imbalance in the Compulsory Pension Insurance System: the Case of Russia - A. l. Safonov; Yu. V. Dolzhenkova (Финансы: теория и практика, 2020)
The aim of the article is to study the impact of tax and tariff policy on the financial balance of the compulsory pension insurance system in Russia, as well as to substantiate proposals for its financial stabilization. The authors analyzed the consequences of regression applied on wages while forming tariffs for pensions. The methods used in this study were economic, statistical and empirical methods, analysis and synthesis, abstraction, systemic-structural approach. The authors analyzed the influence of preferential tariffs for certain types of economic activity and the use of simplified tax systems for organizations on the income of the Pension Fund of the Russian Federation. The work contains the calculation of income shortfalls in the compulsory pension insurance system resulting from the use of regression and tax benefits when calculating insurance payments to the budget of the Pension Fund of Russia. The authors estimated the financial consequences of the pension valorization in the Soviet period and the pension indexation policy in Russia resulted in the rising costs of the Pension Fund of Russia. The conclusion is that the current procedure for determining insurance contributions to the Pension Fund of the Russian Federation, which provides for a large number of benefits, does not correspond to generally accepted world practice and creates major risks for the financial balance of the pension system. This may cause increasing poverty among seniors. Raising the retirement age did not solve the problem of balancing the pension system, but exacerbated it. The regression in the payment of insurance premiums led to a conundrum in Russia, when an increase in wages resulted in the decrease of the Pension Fund of the Russian Federation’s income. This is associated with the precarization of wages and the desire of business to minimize tax payments. The prospect of further research is to study the conditions for financial stabilization of compulsory pension insurance during the Russian economic crisis. The analysis showed that there is a need to create an independent actuarial center for setting tariffs for deductions to the Pension Fund of the Russian Federation, as well as the redistribution of areas of responsibility between the Pension Fund of the Russian Federation and the Ministry of Finance of Russia.